2020
DOI: 10.1186/s12893-020-00885-7
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 on gastric cancer surgery: a single-center retrospective study

Abstract: Background The coronavirus disease 2019 (COVID-19) has been declared a global pandemic by the World Health Organization. Patients with cancer are more likely to incur poor clinical outcomes. Due to the prevailing pandemic, we propose some surgical strategies for gastric cancer patients. Methods The ‘COVID-19’ period was defined as occurring between 2020 and 01-20 and 2020-03-20. The enrolled patients were divided into two groups, pre-COVID-19 group (PCG) and COVID-19 group (CG). A total of 109 patients with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 20 publications
1
24
1
Order By: Relevance
“…Patients worried about the tumor progression in the case of a long preoperative waiting time, especially during the coronavirus disease 2019 (COVID-19) pandemic, when the preoperative waiting time was prolonged. 24 In this study, we found that the long-waiting group had a shorter postoperative hospital stay than the short-waiting group, however, a significant difference was not found in terms of complications and long-term survival. The cause of the shorter postoperative hospital stays of the long-waiting group remained unclear, and adequate preoperative preparation might shorten the postoperative hospital stay.…”
Section: Discussioncontrasting
confidence: 48%
“…Patients worried about the tumor progression in the case of a long preoperative waiting time, especially during the coronavirus disease 2019 (COVID-19) pandemic, when the preoperative waiting time was prolonged. 24 In this study, we found that the long-waiting group had a shorter postoperative hospital stay than the short-waiting group, however, a significant difference was not found in terms of complications and long-term survival. The cause of the shorter postoperative hospital stays of the long-waiting group remained unclear, and adequate preoperative preparation might shorten the postoperative hospital stay.…”
Section: Discussioncontrasting
confidence: 48%
“…But the number and composition of diseases that admitted patients had changed markedly. The proportion of patients with ovarian cancer admitted to our department rose by 20% during the CG and SOCG periods, with a significant increase in the local patients admitted; both could be attributed to travel restrictions and blockades in Beijing ( 3 ).…”
Section: Discussionmentioning
confidence: 94%
“…Ovarian cancer is a common gynecologic malignancy and often progresses to an advanced stage at the visit of the patient. During the epidemic, the Beijing municipal government limited the access of patients and the time of pre-hospital examination was prolonged ( 3 ), which may delay the prognosis of ovarian cancer. In turn, it leads to more incredible surgical difficulty, more significant surgical comorbidities, greater blood loss, and greater expenses ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Twelve studies were reviewed for elective surgery outcomes during the COVID-19 pandemic ( Table 2 ) [ 16 17 19 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 ]. All of these reports presented postoperative morbidity and mortality data that were comparable to the pre-pandemic era.…”
Section: Resultsmentioning
confidence: 99%
“…Clinicians must treat cancer patients in accordance with their individual characteristics, the involved organ(s), the tumor stage, and the available adjuvant treatments. Although some studies have indicated an increase in T4 stage cancer during the pandemic, most have reported no significant upstaging in terms of the TNM classification ( Table 3 ) [ 8 28 33 57 58 59 60 61 62 63 ]. A hasty or obstinate selection of surgical resection is thus unnecessary in positive COVID-19 cases if other treatment modalities are available.…”
Section: Resultsmentioning
confidence: 99%